2019
DOI: 10.3399/bjgp19x706853
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of chest X-ray for detecting lung cancer in people presenting with symptoms: a systematic review

Abstract: BackgroundDespite increasing use of computed tomography (CT), chest X-ray remains the first-line investigation for suspected lung cancer in primary care in the UK. No systematic review evidence exists as to the sensitivity of chest X-ray for detecting lung cancer in people presenting with symptoms.AimTo estimate the sensitivity of chest X-ray for detecting lung cancer in symptomatic people.Design and settingA systematic review was conducted to determine the sensitivity of chest X-ray for the detection of lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 41 publications
3
46
0
3
Order By: Relevance
“…Our findings are consistent with a previous systematic review, which has suggested an estimate of 77 to 80% for the sensitivity of chest radiograph to detect lung malignancy in symptomatic patients. 5 This review did not focus on primary care, and only two studies were performed in a primary-care setting. These studies were also included in our review and analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with a previous systematic review, which has suggested an estimate of 77 to 80% for the sensitivity of chest radiograph to detect lung malignancy in symptomatic patients. 5 This review did not focus on primary care, and only two studies were performed in a primary-care setting. These studies were also included in our review and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The chest radiograph is a key investigation in this approach, as National Institute of Clinical Evidence (NICE) referral guidelines state that any suspicious chest radiograph should provoke a TWR. 4 Systematic review methodology has previously been utilised to investigate the sensitivity of chest radiographs in symptomatic patients, 5 but to date there has been no systematic review assessing diagnostic accuracy of chest radiograph in a primary-care population. A directed investigation is warranted as difference in disease prevalence between primary and secondary care affects test performance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies identified in a systematic review and a subsequently published study have estimated that CXR does not identify lung cancer in approximately 20-25% of cases. (5,6) The pooled number of individuals with lung cancer from these studies is relatively small (n=494) and definitions of positive and negative results was not entirely consistent between studies. Evidence regarding the consequences of false negative CXR results in terms of time to diagnosis, stage at diagnosis and survival is even more limited.…”
Section: Introductionmentioning
confidence: 95%
“…Ze względu na niskie koszty oraz dostępność badania, RTG klatki piersiowej jest często stosowaną techniką. Ograniczeniem metody jest niska rozdzielczość przestrzenna obrazu i brak możliwości oceny miąższu płuc [3,6]. Badanie ce CT jest metodą z wyboru w ocenie guzów płuc, jednakże rzadko stanowi samodzielne narzędzie diagnostyczne, szczególnie w stagingu i restagingu.…”
Section: Omówienieunclassified